2011
DOI: 10.1002/acr.20580
|View full text |Cite
|
Sign up to set email alerts
|

Matched‐cohort study of body composition, physical function, and quality of life in men with idiopathic vertebral fracture

Abstract: Objective. To determine the effect of 6 years of routine management on body composition, physical functioning, and quality of life, and their interrelationships, in men with idiopathic vertebral fracture. Methods. Twenty men with idiopathic vertebral fracture (patients: mean ؎ SD age 58 ؎ 6 years) were age and height matched to 28 healthy controls with no known disease. The primary outcome was skeletal muscle mass (appendicular lean mass by dual x-ray absorptiometry) assessed at 2 visits (0 and 6 years). Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…For example, it has been shown that levels of physical activity [35,36], grip strength [31] and sarcopenia [37] have been associated with HRQoL scores in postmenopausal women. Additionally, physical function domain scores on the SF36 have been associated with objectively measured physical function in men [38] and can be used as a valid measure of disability [39]. Alternatively, it could be the variability in patient expectations of life that contribute towards the differences in PCS and MCS scores over and above other factors entered into the models [40].…”
Section: Discussionmentioning
confidence: 98%
“…For example, it has been shown that levels of physical activity [35,36], grip strength [31] and sarcopenia [37] have been associated with HRQoL scores in postmenopausal women. Additionally, physical function domain scores on the SF36 have been associated with objectively measured physical function in men [38] and can be used as a valid measure of disability [39]. Alternatively, it could be the variability in patient expectations of life that contribute towards the differences in PCS and MCS scores over and above other factors entered into the models [40].…”
Section: Discussionmentioning
confidence: 98%
“…This effect has been demonstrated in joint replacement and spine disease as well as in a number of upper extremity disease states. 1,2,4,9,11,12,[18][19][20][21][22]25,29,30 In some cases, behavioral health interventions are even being offered in conjunction with treatment of the orthopedic condition or as a precondition for surgical treatment. 2,7 In the shoulder, numerous studies have documented the profound impact of biopsychosocial stressors, coping mechanisms, and pain catastrophizing on perception of shoulder pain and disability.…”
mentioning
confidence: 99%
“…Patients with vertebral fracture were reported to have lower muscle mass in some, not all studies . Vertebral fractures were associated with low muscle strength in both sexes and lower functional reach of arms in women, not men . In women, they were associated with abnormal electromyographic activity of trunk and paraspinal muscles .…”
Section: Discussionmentioning
confidence: 98%
“…In 147 patients with vertebral fracture, greater fracture severity was associated with greater disability and pain . Physical capacity was poorer in men with vertebral fracture vs. age‐matched controls . However, these analyses were poorly controlled for potential confounders.…”
Section: Discussionmentioning
confidence: 99%